ISOLATION AND IDENTIFICATION OF ENTEROHEMOLYTIC ESCHERICHIA COLI FROM SLAUGHTERED COW'S LIVER AND LUNG - Adnan M. Al-Rhodan (Basrah Journal of Veterinary Research)
Liver and lung samples (25 for each) were collected from slaughtered cows and examend bacteriologicaly for the presence of Escherichia coli Eosin-Methylene Blue ( EMB ) and MacConkey agar positive culture (15 from liver and 12 from lung) were produced by cultivation of liver and lung samples Escherichia coli presence was confirmed biochemically in 53.3% of liver isolates and in 33.3% of lung isolates. Enterohemolytic activity was detected in 75%of both liver and lung isolates